Indonesia Indonesia: Indonesia - Arinda Safitri; Julia Purnama Sari (Teknosia, 2023)
Payroll Information System (SIPEGA) at PT. PBI Bengkulu City is an information system that can manage salary data at PT. PBI City Bengkulu. PT. PBI Bengkulu City, currently still processing payroll carried out manually requires observation, accuracy, and detailed planning of the entire payroll process. Therefore, the information system. This will help the company in processing salary data. This Information System will be developed with the method of analysis using the waterfall method. The Waterfall model is an orderly or sequential analysis process. The design uses UML, interface design and design. ERD database. So that in this study obtained an information system that can help manage salary data and facilitate reporting.